Analisis dan Strategi Mitigasi Risiko pada Proses Supply chain Produk Crude Palm Oil dengan Menggunakan Metode Supply chain Operation Reference dan Failure Mode and Effects Analysis (Studi Kasus: PT XYZ) - Wulandari, Intan; Sitania, Farida Djumiati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. XYZ, a Crude Palm Oil (CPO) producer, faces challenges such as delivery delays 2-3 times monthly and poor Fresh Fruit Bunch (FFB) quality, including unripe, overripe, or rotten fruits, reducing production yields and profits. To address this, risk management is essential. Using the SCOR model, the study identifies 26 risks across planning, sourcing, production, delivery, and return activities. FMEA evaluates and prioritizes these risks, finding 6 in planning, 7 each in sourcing and production, 4 in delivery, and 2 in return. The Action priority method highlights five high-priority risks: vehicle damage, raw material delays, broken conveyor chains, production process failure s, and main engine damage. Root cause analysis, fishbone diagrams, and assessment of failure Effects support identifying 15 alternative mitigation strategies. This approach aims to minimize disruptions, improve supply chain efficiency, and protect PT XYZ profitability.